Implications of Genetically Modified Food Technology Policies for Sub-Saharan Africa - Anderson, Kym (World Bank, Washington, D.C., 2013)
The first generation of genetically modified (GM) crop varieties sought to increase farmer profitability through cost reductions or higher yields. The next generation of GM food research is focusing also on breeding for attributes of interest to consumers, beginning with "golden rice," which has been genetically engineered to contain a higher level of vitamin A and thereby boost the health of unskilled laborers in developing countries. The authors analyze empirically the potential economic effects of adopting both types of innovation in Sub-Saharan Africa (SSA). They do so using the global economy-wide computable general equilibrium model known as GTAP. The results suggest that the welfare gains are potentially very large, especially from nutritionally enhanced GM wheat and rice, and that-contrary to the claims of numerous interests-those estimated benefits are diminished only slightly by the presence of the European Union's current barriers to imports of GM foods. In particular, if SSA countries impose bans on GM crop imports in an attempt to maintain access to EU markets for non-GM products, the loss to domestic consumers due to that protectionism boost to SSA farmers is far more than the small economic gain for these farmers from greater market access to the EU.